Translating Jinns in Naguib Mahfouz’s Layali Alf Layla into English - Alderbashi, Bilal; Haslina Haroon, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Jinns are an important part of Arabic culture and have been weaved into the texture of the Arabic language and literature; however, the overlap between the different classes of Jinns and the various interpretations of the entities mean that the translator is faced with the problem of non-equivalence when translating Jinns into another language. Taking this into account, the aim of this study is to determine the strategies used in the translation of four different classes of Jinns in Naguib Mahfouz’s Layali Alf Layla into English. To conduct the study, the Arabic lexical items are extracted, listed, and described in the light of their cultural and linguistic background. Their counterparts in the English translation, Arabian Nights and Days, are also located and discussed, taking into consideration their cultural and linguistic background. The pairs are then compared in order to identify the relationships between the corresponding items and to examine the translation strategies employed. The strategies for dealing with non-equivalence as proposed by Baker (2018) are used as a framework for analysis. The results show that the translator employed the use of strategies such as translation by a cultural substitution, a related word, a less expressive word and omission when rendering the supernatural beings into English. The study concludes that understanding the nature of the Jinns in the source text and the different levels of meaning carried by each supernatural being can assist the translator in finding the most suitable equivalent in the target language for the different classes of Jinns.